Quantification of social cost at product price-level for urban freight: a study of industrial products. (6th March 2020) - Kumar, Chitresh; Ganguly, Anirban
The urban area largely relies on the movement of goods and services. Additionally, pollution and congestions, the two negative externalities of urban freight movement, has led to a plethora of restrictions and regulations from operational and supply chain perspective. The paper tries to develop a bi-level programming model to analyse the social cost of pollution and congestion due to freight movement within urban areas of India at the product unit price-level. The model was based on government's toll and time-windows based regulation for vehicular entry restrictions within the urban areas for pollution. The model was iterated for various buyer-supplier for various buyer-supplier scenarios and for different service levels for backorders and deliveries during restricted time windows. It was observed that for various levels of service, profit differential varied between (−1.7%) to 2.8% of the product unit price and seemed to be significant enough for supply chain policy consideration.